2000
DOI: 10.1046/j.1365-2354.2000.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of cancer patients, their family members and health professionals toward active euthanasia

Abstract: This qualitative study describes the attitudes of four groups of people in cancer care toward active euthanasia. Patients (32) with incurable cancer, their family members (13), nurses (13) and physicians (13) participated in the study which was carried out in two central hospitals and in four health centres in Finland. The data was collected by means of focused interviews which were taped, transcribed and then analysed by content analysis. More than half of the participants said that they could ethically justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 17 publications
7
64
0
3
Order By: Relevance
“…The thirty studies comprised eighteen quantitative studies, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] nine qualitative studies, [30][31][32][33][34][35][36][37] two literature reviews, 2 3 and one anthropological account of euthanasia practice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thirty studies comprised eighteen quantitative studies, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] nine qualitative studies, [30][31][32][33][34][35][36][37] two literature reviews, 2 3 and one anthropological account of euthanasia practice.…”
Section: Methodsmentioning
confidence: 99%
“…These findings of a correlation between palliative care and a lower support for euthanasia are corroborated neither by Kuhse and Singer, 20 nor by Kuupelomäki. 31 Verpoort et al's 36 findings showed that while the majority of Belgian palliative care nurses expressed negative attitudes toward euthanasia, they were not a priori for or against euthanasia. Overall, their attitudes tended to mirror the dynamics of clinical practice and could change depending on the situation of each individual patient.…”
Section: Arguments For or Against Euthanasiamentioning
confidence: 99%
“…Kuuppelomäki'nin yaptığı bir çalışmada hemşirelerin %62,0'si ve hekimlerin %46'sı aktif öta-naziye olumlu baktıklarını belirtmiştir [21]. Yurt dışında yapılan çalışmalarda ötanaziyi destekleme oranı %60 ile %90 arasında değişmektedir [22,23].…”
Section: Discussionunclassified
“…4 The perceptions of registered nurses (RNs) have been rarely explored, although findings from countries that have legalized euthanasia emphasize their significant role in the process. [11][12][13][14] Since 2000, only 2 studies have explored Finnish nurses' views of euthanasia, 4,15 although its legalization would potentially affect more than 50 000 nurses in Finland. 16 …”
mentioning
confidence: 99%